Developing a Social Media Marketing Plan for 90 Degrees Construction and Architecture Company Limited - Tran, Thi Tram (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Digital Marketing; 2021-2025.